1994
DOI: 10.1079/bjn19940005
|View full text |Cite
|
Sign up to set email alerts
|

Total energy expenditure and energy intake in the pre-school child: a comparison

Abstract: In a cohort (n81) of healthy children aged 1.5-4.5 years, measurements of energy intake and energy expenditure were compared. Energy intake was calculated following a 4 d weighed record completed by the mother or guardian of the child. Total energy expenditure was measured using the doubly-labelled water technique. Mean energy intake and expenditure in the cohort were 4773 kJ/d and 4928 kJ/d respectively. The mean relative bias between the techniques was 154 kJ/d. In the older children (3.545 years) the mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(106 citation statements)
references
References 9 publications
11
93
1
1
Order By: Relevance
“…Although good agreement between measured metabolizable intake and observed energy intake calculated from dietary intake assessment methods has been demonstrated (Davies et al, 1994), several other studies have reported underestimations of habitual intake Livingstone et al, 1990Livingstone et al, , 1992Schoeller et al, 1990;Black et al, 1997). Work by Davies et al (1994) and the present study indicate a moderate but not signi®cant bias of weighed food records against doubly labelled water in infants and young children. However, there are a number of reasons why absolute agreement between these methods is not to be expected.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Although good agreement between measured metabolizable intake and observed energy intake calculated from dietary intake assessment methods has been demonstrated (Davies et al, 1994), several other studies have reported underestimations of habitual intake Livingstone et al, 1990Livingstone et al, , 1992Schoeller et al, 1990;Black et al, 1997). Work by Davies et al (1994) and the present study indicate a moderate but not signi®cant bias of weighed food records against doubly labelled water in infants and young children. However, there are a number of reasons why absolute agreement between these methods is not to be expected.…”
Section: Discussionsupporting
confidence: 63%
“…Accuracy of the WI method has been considered in preschool children aged 1.5 ± 4.5 y using doubly-labelled water as a reference (Davies et al, 1994). These authors concluded that the WI method was acceptable for assessing dietary intake in groups but not in individuals.…”
Section: Introductionmentioning
confidence: 99%
“…We applied the equation published by Davies et al (1994) with the assumption that 20% of total water losses are fractionated. However, inaccurate assumptions regarding the proportion of fractionated water losses have only minor effects on results obtained by the DLW method (Vasquez-Velasquez, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Isotope enrichment in dose and urine samples was analysed using a Sira dual inlet mass spectrometer (Hoffman et al, 2000). Carbon dioxide production was calculated according to Davies et al (1994), assuming that 20% of total water losses were fractionated. Isotope dilution spaces were calculated from the zero-time enrichments obtained from the exponential isotope disappearance curves that provided estimates for the rate constants, k d and k o , for 2 H and 18 O, respectively.…”
Section: Anthropometric Measurementsmentioning
confidence: 99%
“…Total energy expenditure was measured over a 14 d period via the DLW technique as described in detail elsewhere (Davies et al, 1994). Energy intake was assessed using a four day weighed dietary record.…”
Section: Subjectsmentioning
confidence: 99%